Studies in Social Roots of the Police Informal Economic Activity - Анастасия Евгеньевна Дубова (Journal of Economic Sociology, 2011)
The article describes the academic literature on social roots of police involvement into informal economy. The major issue for investigation is: why do policemen move from law enforcement officers into market actors? Does it result from group norm socialization or their individual characteristics? Three concepts involving individual, group and system factors are introduced. Attempts to adapt approaches applied in sociology of deviant behavior (social criminology) to economic sociological tasks are undertaken. In conclusion, potential trajectories for the future research of these issues are indicated. полиция